Whose domain and whose ontology? Preserving human radical reflexivity over the efficiency of automatically generated feedback - Beattie, Amanda Russell; Hayes, Sarah; Jandri´ć, Petar (Proceedings of the International Conference on Networked Learning, 2018)
There are some forms of feedback in daily life that, though generated and delivered via a machine, we may welcome, because they help us to function with ease. For example, being provided with explicit directional instructions from a Sat Nav can save time and embarrassment from being late. Automatic tills in supermarkets mean we can empty loose change into these to pay for things, and the amount is calculated on our behalf, with change efficiently dispensed. Feedback on our bank balances from cash machines may not always be welcome…, but there are advantages in terms of practicality. In this article we challenge however, the uncritical application of similar algorithmic processes for providing automatically generated feedback for students in Higher Education (HE). We contest this on the basis that the human side of feedback appears to be giving way to the non-human, as e-technologies and their algorithmic affordances are expected to meet the demands that emerge from within a neoliberal framing of contemporary HE. Initially we examine developments of Artificial Intelligence (AI), and the e-marking platform Turnitin to question where we might locate a student voice? We point to the way that networked learning intersects across developments in technology and radical pedagogies to support this concern. We then draw on our own relational, and lived, experience which produces feedback that emerges from within an illicit exploration of our own vulnerabilities as academics, as students, and friends, in a demonstration of performing radically reflexive feedback. Finally, we advocate for the creative potential of an autoethnographic research method and exploration of mindfulness practices aligned with teaching and learning journeys. These cannot and should not be reduced to the ‘sat-nav experience’ in terms of feedback. We suggest that, as technology becomes ever more intimately embedded into our everyday lives, generic (but power-laden) maps are incorporated into both student and staff ‘perceived’ space. A radically reflexive form of feedback may not follow a pre-defined route or map, but it does offer a vehicle to restore student voices and critical self-navigation that is absent, but very much needed, in the ongoing shaping of contemporary HE.